Effects of coupling agent on dielectric properties of PTFE based and Li2Mg3TiO6 filled composites. Issue 16 (November 2019) - Luo, Fuchuan; Tang, Bin; Fang, Zixuan; Yuan, Ying; Li, Hao; Zhang, Shuren
Abstract: In this study, Li2 Mg3 TiO6 (LMT) ceramic powders were synthesized by conventional solid state route, optimized using perfluorooctyltriethoxysilane (F8261) and then loaded into polytetrafluoroethylene (PTFE) emulsion. The effects of F8261 on the surface characteristics of LMT particles were investigated by analyzing SEM, XPS and contact angle. After the coating of F8261, the surface energy of LMT was decreased, leading to a more compatible microstructure with PTFE matrix than untreated LMT particles. As a comparison, the untreated and optimized LMT/PTFE composites were fabricated with different content of LMT (ranged from 30 wt % to 70 wt %). As compared to untreated samples, the substrates loaded with F8261 optimized LMT exhibited better properties with higher dielectric constant and lower dielectric loss. Furthermore, the dielectric constant of optimized LMT filled composites matched well with the values calculated by Effective medium theory (EMT). The temperature coefficient of dielectric constant ( τ ε ) of the composites were theoretically discussed. Finally, F8261 optimized LMT/PTFE composites performed prominent dielectric properties of ε r = 6.17, tan δ = 0.0019 and τ ε = 123 ppm/°C at high optimized LMT loading of 70 wt %.